Chapter Alexander von Humboldt, da 250 anni il teorizzatore dello studio interdisciplinare dell'ambiente - Benincasa, Fabrizio (Proceedings e report, 2020)
In 19th century birth of the term scientist led to beginning of Sciences professionalization and end of Nature eclectic scholar, of which Humboldt was the last exponent. Humboldt managed to connect all disciplines in a holistic vision of the world: organic and inorganic nature form a single system of active forces; all the organisms of Earth are linked as a family sharing same home. Today, given the anthropogenic damage caused to Nature, it needs to reconsider his unified vision, establishing connections between scholars of various disciplines, for an organic and global vision of Environment.